Kobieta w zakładzie pracy w Polsce Ludowej i po 1990 r. Analiza stanu prawnego - Kosztowna, Natalia (Annales. Etyka w Życiu Gospodarczym, 2016)
The article deals with the mechanisms of female employment. The author has setherself the task of comparing the conditions of employment of women during thePolish People’s Republic (PRL) and contemporary times. The main aim was to indicatethe evolution of labour law relating to women workers from a series of instructionsand regulations of the Council of Ministers defining the protection ofwomen's work before 1974, through a variety of general rules applicable to all employees,to the regulations contained in the Labour Code and also current legislation.The article attempts to assess the ethical actions taken by the state to improvethe conditions of employment of women in the workplace. The text indicates theimportance of the work in the lives of women. Occupational status and income levelstrongly influenced the behaviour of women, who in many cases took up work intendedonly for men due to the fact that during PRL it was only such work whichwould allow them to obtain a higher salary. The article indicates that today there isa special emphasis placed on the prohibition of restricting the employment ofwomen in jobs and on the conditions of the employment of pregnant women.The author of this article has evaluated the legislation introduced by the state,which contributed to the increase in female activity in the labour market. However,in ethical terms of ethical it is very difficult to unambiguously assess the actionstaken by the state for the protection of women's work in the PRL, but also in contemporarytimes.